OMALIZUMAB IN TREATMENT FOR ALLERGIES - T.V. Kulichenko (Union of pediatricians of Russia, 2007)
Omalizumab, whose active basis is recombinant, human, monoclonal antibodies to Ige, gives a unique therapeutic field in treatment for allergies. The present medication constitutes neutralizing antibodies, connecting Ige even before any appearance of allergic symptoms. A few years ago, omalizumab has been approved in treatment for severe, persistent, atopic bronchial asthma among patients with poor control over its run. To day, omalizumab efficacy is studied in therapy for a number of other allergies thanks to its ability to suppress the Ige effect or function. The article highlights the modern experience of anti Ige antibodies application in treatment of adults and children, suffering from atopy.Key words: omalizumab, anti_ige_antibodies, Igе, bronchial asthma, allergic rhinitis, allergen specific immunotherapy, treatment, children.